Metabolomic Profiles for Primary Progressive Multiple Sclerosis Stratification and Disease Course Monitoring - Stoessel, Daniel; Stellmann, Jan-Patrick; Willing, Anne; Behrens, Birte; Rosenkranz, Sina C.; Hodecker, Sibylle C.; Stürner, Klarissa H.; Reinhardt, Stefanie; Fleischer, Sabine; Deuschle, Christian; Maetzler, Walter; Berg, Daniela; et al. (Frontiers in Human Neuroscience, 2018)
Primary progressive multiple sclerosis (PPMS) shows highly variable disease progression with poor prognosis and a characteristic accumulation of disabilities in patients. These hallmarks of PPMS make it difficult to diagnose and currently impossible to efficiently treat. This study aimed to identify plasma metabolite profiles that allow diagnosis of PPMS and its differentiation from the relapsing-remitting subtype (RRMS), primary neurodegenerative disease (Parkinson´s disease (PD)) and healthy controls (HC) and that significantly change during the disease course and could serve as surrogate markers of MS-associated neurodegeneration over time. We applied untargeted high-resolution metabolomics to plasma samples to identify PPMS-specific signatures, validated our findings in independent sex- and age-matched PPMS and HC cohorts and built discriminatory models by partial least square discriminant analysis (PLS-DA). This signature was compared to sex- and age-matched RRMS patients, to patients with PD and HC. Finally, we investigated these metabolites in a longitudinal cohort of PPMS patients over a 24 month period. PLS-DA yielded predictive models for classification along with a set of 20 PPMS-specific informative metabolite markers. These metabolites suggest disease-specific alterations in glycerophospholipid and linoleic acid pathways. Notably, the glycerophospholipid LysoPC(20:0) significantly decreased during the observation period. These findings show potential for diagnosis and disease course monitoring, and might serve as biomarkers to assess treatment efficacy in future clinical trials for neuroprotective MS therapies.